The link and match of the demand and supply for productive vocational school teachers with regard to spectrum of vocational skills in the perspective of education decentralization - A.G. Tamrin; S Slamet; S. Soenarto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The purpose of this study was to describe the pattern of link and match of the demand and supply for productive vocational school teachers which should be carried out in the future. This study is descriptive qualitative with the grounded theory approach. The unit of analysis consisted of: policy makers at central level; policy makers at local level; productive vocational school teachers; Teacher Education Institutes (LPTK), and Non-Teacher Education Institutes (Non-LPTK). The data were analyzed using the three phases: open coding, axial coding, and selective coding. The research results are as follows. (1) The pattern of the demand for productive vocational school teachers has been fulfilled through such programs as Three Year Diploma for Vocational Teacher of Engineering, Bond-based Remuneration for Bachelor's Level, Civil Servant Recruitment, Regional Civil Servant Recruitment, and Non-permanent Teachers. (2) Productive vocational school teachers supplied included LPTK graduates majoring in 22 vocational skills training programs and Non-LPTK graduates majoring in 45 vocational skills training programs out of 48 programs. (3) Productive vocational school teachers were distributed in three types of programs. (4) A system of vocational teacher education was conducted by increasing and refining. (5) Link and Match pattern of demand and supply for productive vocational school teachers involved integration of supply for LPTK graduates and that of Non-LPTK graduates, the distribution of such supply, and the pattern of implementation of vocational teacher education.